PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DENGAN MODEL CONTEXTUALTEACHING LEARNING - Manurung, Rosmasi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Based on the preliminary research and observation to the fourth grade students at SDN 01 Murni Panti in Pasaman Regency, there was the students’ outcomes was low caused most of the teachers still used conventional method in learning. So, that’s way the author would like to improve their outcomes in learning Civic Education (PKn) through the research entitled: “Peningkatan Hasil Belajar Siswa dalam Pembelajaran Pendidikan Kewarganegaraan dengan MenggunakanModel Contextual Teaching Learning di Kelas IV SDN 01 murni panti kecamatan panti Kabupaten Pasaman”. The purpose of this research was to describe the students’ improvement in learning Civic Education through Contextual Teaching and Learning. This research was Classroom Action Research used qualitative and quantitative approach. This research has been done in two cycles completed by the planning, action, reflection, and students’ learning outcomes. Based on the research, it can be concluded that the student’s learning outcome has been improved, it can be seen from their result both of the teacher’s activities and students’ activities, as described: in designing a lesson plann was 60.71% (cycle I) and increased to 83.93% (cycle II); the teacher’s activities was 58.33% (cycle I) and increased to 84.73% (cycle II); the students’ activities was   55.56% (cycle I) and increased to   83.34% (cycle II); while the students’ learning outcomes was 64.27 (cycle I) increased to 80.53 (cycle II). Kata Kunci: hasil belajar; pendidikan kewarganegaraan; contextual teaching learning